ЭТАПЫ ФОРМИРОВАНИЯ ИНВЕСТИЦИОННОГО ПОРТФЕЛЯ ПРЕДПРИЯТИЙ (Journal of Economic Research & Business Administration, 2015)
In this article considered stages of formation of an investment portfolio of the enterprises.